Design of a new torque standard machine based on a torque generation method using electromagnetic force. (20th December 2016) - Nishino, Atsuhiro; Ueda, Kazunaga; Fujii, Kenichi
Abstract: To allow the application of torque standards in various industries, we have been developing torque standard machines based on a lever deadweight system, i.e. a torque generation method using gravity. However, this method is not suitable for expanding the low end of the torque range, because of the limitations to the sizes of the weights and moment arms. In this study, the working principle of the torque generation method using an electromagnetic force was investigated by referring to watt balance experiments used for the redefinition of the kilogram. Applying this principle to a rotating coordinate system, an electromagnetic force type torque standard machine was designed and prototyped. It was experimentally demonstrated that SI-traceable torque could be generated by converting electrical power to mechanical power. Thus, for the first time, SI-traceable torque was successfully realized using a method other than that based on the force of gravity.